2021
DOI: 10.3390/nu13113966
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Dietary Patterns among the Polish Elderly: A Challenge for Public Health

Abstract: The aim of the study was to assess the diversity of dietary patterns within the elderly, in relation to the region of residence, household structure, and socioeconomic status. The questionnaire was conducted in a group of 427 Polish adults aged 60 and older from June to September 2019. The sample was selected by means of the snowball method in two regions. Principal component analysis (PCA) was used to extract and identify three dietary patterns (factors) from the frequency of eating 32 groups of foods. Logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…Among Chinese older people, we creatively revealed the association between LA and DD, with those living with family members versus those living in nursing homes being more likely to have a higher intake of eggs, milk, vegetables, etc., and less salt-cured vegetables and sugar. This result is consistent with the ndings of a study on Polish older adults [34]. It has been suggested that the sociodemographic characteristic of living alone is associated with health organizations, health policy makers, and health care professionals such as dietitians, and thus nutritional behavior may be directly in uenced by LA.…”
Section: Discussionsupporting
confidence: 90%
“…Among Chinese older people, we creatively revealed the association between LA and DD, with those living with family members versus those living in nursing homes being more likely to have a higher intake of eggs, milk, vegetables, etc., and less salt-cured vegetables and sugar. This result is consistent with the ndings of a study on Polish older adults [34]. It has been suggested that the sociodemographic characteristic of living alone is associated with health organizations, health policy makers, and health care professionals such as dietitians, and thus nutritional behavior may be directly in uenced by LA.…”
Section: Discussionsupporting
confidence: 90%
“…‘High-processed food, meat and confectionery’ DP is characterized by frequent high consumption of light bread and less frequently consumed fried food, meats, pork and sweets. This pattern resembles traditional Polish cuisine, with white flour products, fried foods, fatty meats and sweets [ 44 , 45 ]. Frequent ingestion of the above-mentioned products is detrimental to health and brain functions ( Table 2 ).…”
Section: Discussionmentioning
confidence: 98%